Influence of Spirituality Leadership Cultures Cognitive Processes Personal Attitude To Leadership Integrity Through Decision Making In Lembang District Tana Toraja And Toraja – North, Indonesia - Goti, Matius (International Journal of Scientific Research and Management (IJSRM), 2024)
Abstract: This research was conducted to see the intricate relationships between spirituality, local leadership cultures, cognitive processes, and personal attitudes towards leadership integrity, specifically through decision-making in Lembang District, Tana Toraja, and Toraja Utara in Indonesia. These regions are renowned for their rich cultural heritage and unique leadership traditions deeply rooted in spirituality.  Data collection was achieved through the distribution of questionnaires to various respondents. The gathered data were analyzed using multiple linear regression techniques. The findings reveal that To Parenge''s leadership spirituality, personal attitude and decision-making significantly influence To Parenge''s leadership integrity, decision-making in the ten Lembang in Tana Toraja and North Toraja regencies.